Effects of a multi-level intervention on pedestrians’ behavior among Iranian health worker supervisors: a randomized controlled trial - Harzand-Jadidi, Sepideh; Vatandoost, Maryam; Schwebel, David C.; Sadeghi-bazargani, Homayoun; Bakhtari Aghdam, Fatemeh; Allahverdipour, Hamid (Frontiers in Public Health, 2025)
BackgroundPedestrian injury is a global public health concern. Multi-level community-based health education campaigns offer promise to reduce the burden. The current study investigated the effect of a multi-level intervention based on the socio-ecological model (SEM) to improve pedestrian safety by training health worker supervisors in Iran, with the expectation that they would disseminate their learned knowledge more broadly in the population.MethodsEighty-two health worker supervisors in Tabriz, Iran were randomized to an intervention or control group, with 41 assigned to each group. Participants in the intervention group received both live pedestrian safety education and offline training through a virtual WhatsApp group. Messages, pictures, and short videos about pedestrian safety were sent to participants, and solutions were discussed in the group settings. The control group had no training. Self-reported pedestrian behavior was assessed before and after the intervention.ResultsAt baseline, there were no significant differences between the intervention (82.48 ± 8.54) and control (81.05 ± 8.55) groups in pedestrian behavior scores (t = 2.01, p = 0.001). After the intervention, the average score of pedestrians’ behaviors of the intervention group increased significantly compared to the control group (87.98 ± 5.83 vs. 80.37 ± 9.03), (t = 3.61, p = 0.0002). All five subscale scores of PBQ, including adherence to traffic rules and recommendation, violations, positive behaviors, distraction, and aggressive behaviors showed similar and significant changes in the intervention group compared to control group.ConclusionApplication of a multi-level intervention based on the socio-ecological model improved self-reported pedestrian behavior of health worker supervisors. Using multi-level interventions by targeting health workers, who then disseminate their learning to the public, could enhance pedestrian safety across society.